Prosedur Pelayanan Dokumen Notice Of Readiness Kapal Bermuatan Batu Bara Pada PT. Armada Lintas Barunabandar Lampung - Ovis Nirmawanda Laia; Dirhamsyah Dirhamsyah; Dina Rispianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explain the procedure for processing the Notice of Readiness (NOR) document for coal-carrying vessels at PT. Armada Lintas Baruna Bandar Lampung and to identify the consequences that occur when the NOR is submitted late or contains inaccuracies. As vessels from international shipping companies frequently call at Indonesian ports to transport coal abroad, companies must continuously improve service efficiency and reliability to support national shipping and trade performance. PT. Armada Lintas Baruna plays a key role in managing export vessels, particularly coal carriers, from loading ports to their country destinations, and the NOR serves as a crucial document through which the Ship Master declares that the vessel is fully prepared to load or discharge cargo during the charter period. The NOR service process includes several stages: verification of vessel readiness by the agent, preparation and submission of the NOR document, verification by the port authority, issuance of NOR confirmation, and document closing. Delays or errors in NOR submission can disrupt the vessel’s operational schedule, potentially causing financial losses for shipowners through demurrage charges. This paper employs both field research and library research to provide an in-depth understanding of the NOR service mechanism.